Rapid bioremediation of Alizarin Red S and Quinizarine Green SS dyes using Trichoderma lixii F21 mediated by biosorption and enzymatic processes - Liyana Amalina Adnan; Palanivel Sathishkumar; Abdull Rahim Mohd Yusoff; Tony Hadibarata; Fuad Ameen (Springer-Verlag Berlin Heidelberg, 2024)
Non-Indexed Publication